Are you Covidient or Covidiot?: A Linguistic Landscape Study on COVID-19 flyer in Pasuruan District - Insyirah, Athala; Sudarwati, Emy (Yayasan Visi Intan Permata, 2021)
Although previous studies on linguistics landscape are quite numerous in number, linguistics landscape issue in relation to the COVID-19 flyer is still untouched. The current study aims to shed a light on the phenomenon of multilingualism on the linguistics landscape in relation to the COVID-19 flyer in Pasuruan district. This study focuses on the usage of language on the COVID-19 flyer in Pasuruan, the impression of society regarding this linguistics signs, and the preference of linguistics signs used on the COVID-19 flyer. The research was done by capturing all linguistics signs related to COVID-19 in Pasuruan district to be analyzed in terms of its type. The researchers also distributed the online questionnaire via social media to get the society’s perception regarding the COVID-19 linguistics sign found in flyers and to get some information regarding the preferred language used on the flyers. It was revealed that monolingual, bilingual, and multilingual signs appear on COVID-19 flyers. In addition, the majority of society views positively the multilingualism phenomena on the COVID-19 flyer as it serves as intelligible, educational, and effective means of campaign to halt the spread of the virus. All in all, both Bahasa Indonesia–English are favorable languages to be used to deliver messages related to COVID-19 issue.